A Brief Survey of Modern Protestant Literary Missions in Guangzhou - HE Zhangrong (Journal of Research for Christianity in China (JRCC), 2025)
Literary work was one of the five major areas of missionary activity undertaken by modern Western Protestant missionary societies. Protestant literary work in Guangzhou over the past century or so can be broadly divided into two phases. Phase One: 1807–1842. This marked the arduous pioneering period for Protestantism in Guangzhou, during which its literary work also began its difficult initial stages. The second phase: 1842–1920s. Following the Opium Wars, Protestant literary missions in Guangzhou entered a period of vigorous development. Alongside medical, educational, and charitable endeavors, literary work became central to the missionaries’ overall efforts, yielding significant achievements. The social, cultural, and political impact of the missionaries’ literary work far exceeded its religious influence. It played an indispensable role in propelling Lingnan society—and indeed Chinese society as a whole—toward the threshold of modernity.